Participación de los jóvenes como candidatos en las elecciones seccionales del Cantón Loja, en los periodos 2009 y 2014 - Aguirre Rojas, Carmen Jacqueline (2019)
The present research work called “Participation of young people as candidates in the sectional elections of Canton Loja, in the periods 2009 and 2014”, had the purpose of knowing to what extent young people participate in electoral processes, what were the results they obtained and the factors that favored such inclusion. The importance of it lay in offering a description of this social phenomenon that has been widely debated, but of which there was little empirical evidence. The main contribution not only contributed in the academic field by filling this theoretical gap, but also provided elements for political analysis in political organizations and electoral behavior. The methodological approach that was used was of a mixed nature, it included an unpublished database, which was built according to the candidates who participated in the electoral processes of the 2009 and 2014 periods of the Loja canton, since prior to this work there were no studies or databases carried out with the necessary parameters to quantitatively substantiate this research. Interviews were also applied to actors who participated as candidates, in order to obtain more information and triangulate it. Among the most important results, it is highlighted that the level of participation of young people is considered low, with a percentage that reached 37%. Among the political elements that favor participation are the spaces of parish boards, political movements, and candidacies as alternates. Gender is mainly influenced by social issues, since young women are the ones that are most included in the lists of candidates.